La photographie au service de l’Église - Sylvaine Guinle-Lorinet; Paul Bernadou (Communication)
Over time, photography enables to capture the Catholic Church’s representations of the very heart of Lourdes’ Marian sanctuary : the Grotto. To each period in the history of the sanctuary there corresponds a precise image, created by the Church and conveyed through photography ; from the matrix of a primeval beginning there evolves a sense of sacredness surrounding the Grotto that gives way to a more present day sober attitude. The images change as the Church tries to adapt its discourse to the faithful.